2012
DOI: 10.1007/s00330-012-2406-5
|View full text |Cite
|
Sign up to set email alerts
|

Cystic versus predominantly cystic thyroid nodules: efficacy of ethanol ablation and analysis of related factors

Abstract: • Ethanol ablation under ultrasound guidance is increasingly used for cystic thyroid nodules. • EA seems effective for cystic and predominantly cystic nodules, especially cystic nodules. • The effectiveness of EA was reduced in large or vascular predominantly cystic nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
114
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(125 citation statements)
references
References 31 publications
(72 reference statements)
3
114
1
4
Order By: Relevance
“…Most patients report mild, temporary pain at the site of injection, radiating into the neck, chin and ears, due to leakage of a little ethanol into the subcutaneous tissues. In different studies, the pain was reported in 2.5% to 30% or, in large cysts, even 70% of patients 14,18,21 . Occasionally, temporary vocal fold paralysis and dysphonia or, rarely, transient thyrotoxicosis may occur 22 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Most patients report mild, temporary pain at the site of injection, radiating into the neck, chin and ears, due to leakage of a little ethanol into the subcutaneous tissues. In different studies, the pain was reported in 2.5% to 30% or, in large cysts, even 70% of patients 14,18,21 . Occasionally, temporary vocal fold paralysis and dysphonia or, rarely, transient thyrotoxicosis may occur 22 .…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, when using the less frequent ethanol aspiration approach, the ethanol is left in the cavity for 2 to 10 min 8,14,17 . The amounts of ethanol administered during PEI procedures ranged from 36% to 100% of the initial cyst volume in various studies, such as those by Bennedbaek 5,8,14,15,[18][19][20] ). Although most authors do not recommend to administer a single dose of more than 10 mL of ethanol, Kim DW et al injected amounts equal to 100% of the volume of cysts smaller than 20 mL, that is, up to 20 mL of absolute ethanol and, in one case of an extremely large 135-mL cyst, even as much as 30 mL of ethanol 14 .…”
Section: Discussionmentioning
confidence: 99%
“…After skin sterilization and anesthesia with 2% lidocaine at the puncture site, a 16-or 18-ga needle was inserted into the cystic portion of the thyroid nodules through the isthmic area (this is the so-called transisthmic approach) to prevent leakage of fluid or ethanol. 6,18,25 After the needle tip was placed into the cystic portion, as much of the internal fluid as possible was aspirated. If active bleeding was detected during the aspiration of the internal fluid, the aspiration was stopped and 99% ethanol was injected slowly into the cystic space to control the bleeding (On-line Video).…”
Section: Methodsmentioning
confidence: 99%
“…After 2 minutes of ethanol retention, as much of the injected ethanol as possible was removed. 18 After real-time US confirmed that the bleeding had stopped, RF ablation was initiated. On the basis of previous experience, the RF ablation was performed by using a transisthmic approach and the moving-shot technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation